Security concerns and conflict experience of physically disabled people in The Czech Republic - Chvátalová, Jitka; Skotáková, Alena; Reguli, Zdenko (Studia sportiva, 2023)
People with disabilities are more vulnerable to violence than their non-disabled counterparts. The fear of crime increases with the experience of victimization. There are many attempts to enhance the confidence of being outside alone or decrease the fear of crime through self-defense courses. The aim of the present study is to determine the level of security concerns in people with physical disabilities and to identify the most frequent crime they are facing. 77 physically disabled people (aged 15 and more; 45 women, 32 men; 5 elementary, 44 secondary, 28 higher educated) participated in the research. 49 participants use mechanic or electric wheelchair, 19 participants use other compensatory aids, 9 participants do not use any compensatory aids. 35 participants use the assistant service, 42 do not. Data was collected via a questionnaire of four parts, in which participants expressed their security concerns, confidence, or vulnerability in given situations through a 6point scale. Each part of the questionnaire is supplemented by an open question encouraging participants to express their experience. People with disabilities have a slight fear of possible conflict situations. This fear increases in conditions with a greater chance of a potential conflict situation or areas that cannot be left immediately. The results suggest a slight sense of helplessness in verbal conflict situations or a developing conflict that can still be de-escalated. We can assume that people with disabilities feel very vulnerable when it comes to direct physical assault.